Mutilation and theft of library materials in college and university libraries in Region I - Pojas, Elvira Quileban C.; Buenrostro, Juan Jr. C.; Arlante, Salvacion M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1990)
The primary purpose of this study is to identify factors which cause mutilation and theft of library materials in forty-two college and university libraries in Region I. It covers detailed aspects such as the extent of mutilation and theft, factors that influence mutilation and theft, and methods of preventing mutilation and theft of library materials in the libraries of Region I.
In specific terms, this study aimed to : 1. determine the extent of damages inflicted by the library users thru mutilation and theft on books and periodicals; 2. identify the subject fields of books and periodicals which are the most commonly mutilated and stolen; 3. determine if sex, age and frequency of library use are related to acts of commiting mutilation and theft; 4. know which of the personal, social, psychological and situational factors compel students to commit acts of mutilation and theft; 5. determine possible preventive methods to reduce mutilation and book theft; 6. recommend solutions for minimizing acts of mutilation and theft.
The study was conducted from August 10, 1989 to October 5, 1989 and utilized the descriptive normative survey method.
Respondents in this study were undergraduate students who are enrolled on the degree programs for the first semester SY 1989-1990 of the 52,342 of the undergraduate students enrolled in the different colleges and universities in Region I, of which five percent constituted the samples. The students respondents are those coming in the library.
Libraries of Region I has a total of 94 librarians. A total of 73 desk librarians representing the sample responded to the questionnaire survey.
The findings of the study revealed that acts of book mutilation and theft are spontaneous and individual acts. Results suggest that the primary motivation for book theft and mutilation is material deprivation. Certain factors were found to be significantly related to acts of mutilation and theft, and systems can and do provide partial solutions to the problem of unauthorized removal of materials from book and periodicals.
The study noted the identification of factors which causes mutilation and theft and this required the immediate implementation of the following recommendations : 1. There should be strict checking of bags, folders and other personnel effects of outgoing library clietele. 2. There should be designated full-time security guards to check incoming and outgoing library clientele. 3. There should be a depository counter wherein library clientele can deposit their belongings upon entering the library. 4. Availability of materials is of prime importance in the prevention of theft and mutilation. 5. Libraries should conduct periodic inventories. 6. In order to implement the policy which is the reduction on the accessibility of materials the number of books on closed stack should be increased especially those in susceptible categories. 7. Librarian should increase accessibility by initiating loan services, lengthening the borrow period, and allowing a reader to charge out as many books as he requires. 8. Charging desk librarins should not allow new patrons to charge out materials until their applications have been verified. 9. The library should impress upon the freshman students the value of books in education and how mutilation and theft can prove a big hindrance in service. 10. The library should maintain a "Mutilation Register". 11. Familiarity with the interests of the clientele and their habits enables the libraries to fit these interests with the subject of the missing book. 12. The charging systems for books and file material should be made as simple as possible. 13. Library should initiate a low-key public relations program. 14. Attempt to educate the book thief must be personal approach. 15. Every date due slip should bear a slogan to prevent defacement and mutilation. 16. Teaching staff should keep open line of communication with library personnel. 17. Provision on mutilation/theft or violation in the rules and regulations of the institution should be strictly observed whereby any student mutilating a book or taking it from the building without first charging it, would be fined or else suspended or that the damaged copy should be replaced. 18. Library staff must be more accommodating, approachable, friendly to the information needs of the library users. 19. There should be a stamp of ownership of library materials. 20. Besides the physical examinations of book by a person, it is also recommended that mechanical devices can also be used in finding out the mutilated pages. 21. Student government should practice inimical to collective student interests through the student newspapers, discussion and student opinion.
It is further recommended that this study be replicated in other Regions in the country.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Books -- Mutilation, defacement, etc; Libraries, University and college -- Philippines -- Region I